2019
DOI: 10.1007/978-3-030-35802-0_2
|View full text |Cite
|
Sign up to set email alerts
|

Representing Graphs and Hypergraphs by Touching Polygons in 3D

Abstract: Contact representations of graphs have a long history. Most research has focused on problems in 2d, but 3d contact representations have also been investigated, mostly concerning fully-dimensional geometric objects such as spheres or cubes. In this paper we study contact representations with convex polygons in 3d. We show that every graph admits such a representation. Since our representations use super-polynomial coordinates, we also construct representations on grids of polynomial size for specific graph clas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…For proper side contacts, Kleist and Rahman [32] proved that every subgraph of an Archimedean grid can be represented with unit cubes, and every subgraph of a d-dimensional grid can be represented with d-cubes. Evans et al [19] showed that every graph has a contact representation where vertices are represented by convex polygons in R 3 and edges by shared corners of polygons, and gave polynomial-volume representations for bipartite, 1-planar, and cubic graphs.…”
Section: Contact Representationsmentioning
confidence: 99%
“…For proper side contacts, Kleist and Rahman [32] proved that every subgraph of an Archimedean grid can be represented with unit cubes, and every subgraph of a d-dimensional grid can be represented with d-cubes. Evans et al [19] showed that every graph has a contact representation where vertices are represented by convex polygons in R 3 and edges by shared corners of polygons, and gave polynomial-volume representations for bipartite, 1-planar, and cubic graphs.…”
Section: Contact Representationsmentioning
confidence: 99%
“…Gropp [32] positioned the vertices in the plane such that those that form hyperedges are collinear in the plane. Evans et al [33] used polygons to represent hyperedges in 3D to gain additional flexibility.…”
Section: Related Workmentioning
confidence: 99%
“…For proper side contacts, Kleist and Rahman [25] proved that every subgraph of an Archimedean grid can be represented with unit cubes, and every subgraph of a d-dimensional grid can be represented with d-cubes. Evans et al [14] showed that every graph has a contact representation where vertices are represented by convex polygons in R 3 and edges by shared corners of polygons, and gave polynomial-volume representations for bipartite, 1-planar, and cubic graphs.…”
Section: Contact Representationsmentioning
confidence: 99%
“…Together with Proposition 2 this implies the claim. ◀ Evans et al [14] showed that every bipartite graph has a contact representation by touching polygons on a polynomial-size integer grid in R 3 for the case of corner contacts. As we have seen before, side contacts are less flexible.…”
Section: Complete Graphsmentioning
confidence: 99%